Knowledge sharing: Brazilian x Portuguese companies - Oliveira, Mírian (2014)
Companies working in the field of information technology are considered knowledge intensive. Knowledge sharing is one of the most important processes in knowledge management and is related, for example, to increased innovation. Hence, the main aim of this research is to investigate whether country and team tenure are moderators in the relationship between knowledge sharing, absorptive capacity and innovation in information technology companies. For this purpose, this research adopted survey method in which data were collected using a questionnaire sent by e‐mail with a link to the instrument. The 121 responses were divided into three groups: 43 respondents ‐ Brazilian companies operating in Brazil; 41 respondents ‐ Portuguese companies operating in Brazil; and 37 respondents ‐ Portuguese companies operating in Portugal. The countries were selected because they share the same language, and because one is a member of the BRICS group of countries (Brazil, Russia, India, China and South Africa). The data were analysed using Descriptive measures, Exploratory Factor Analysis and Partial Least Squares structural equation modelling. This study confirms the relationship between knowledge sharing and innovation with partial mediation by absorptive capacity and the role of moderators in this relationship. The country of origin of the company was not confirmed as a moderator in the relationship between knowledge sharing, absorptive capacity and innovation, whether the company is located in its home country or not. However, the two countries analysed here are classified as collectivist. Team tenure was identified as a moderator in the relationship (knowledge sharing, absorptive capacity and innovation), in this case, teams with members with up to 12 months on the same team display greater relational intensity. This may occur because when working together for longer, the group’s knowledge may become homogeneous, leading to reduced sharing. The results of this paper will be of use to both corporate managers and scholars.